Diffusion kurtosis imaging: An efficient tool for evaluating age‐related changes in rat brains - Xue‐Fang Han (Wiley, 2021)
Abstract Purpose To evaluate and determine age‐related changes in rat brains by studying the diffusion kurtosis imaging results among different age groups of rats. Methods Sprague–Dawley (SD) rats underwent conventional magnetic resonance imaging (MRI) and diffusion Kurtosis Imaging (DKI). Two diffusion values of mean kurtosis (MK) and kurtosis (K⊥) were measured and analyzed based on laterality, brain regions and age groups. The MK and K⊥ data were plotted against different age groups. Results No laterality was found for the MK or K⊥ values in the cerebral cortex (CT), external capsule (EC), or caudate putamen (CPu) regions. In contrast, significant changes in these values were observed among different age groups. Changes of the MK and K⊥ values were significant in both hemispheres in the EC, the CT, and the CPu brain regions. The changes in the MK and K⊥ values showed a parabolic relationship with ages in all the brain regions. Conclusion No laterality in the MK and K⊥ values was observed for the EC, CT, or CPu regions of the rat brain. Significant changes in MK and K⊥ values were both observed among different age groups, thus suggesting diffusion kurtosis imaging as an efficient tool for studying brain aging in rats.